(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
Seismic modeling was applied to 3D seismic data in order to represent the 3D Permian —Triassic depositional environment, and the Kurrachine Dolomite Formation in the post-Miocene Epoch, Palmyrides- Ash Shaer Area, Syria. The 3D seismic data and the relative acoustic impedance attribute (RAI) were used in this study. This study was carried out in four main stages which are: (1) Seismic interpretation, (2) Building the geological model in time domain, (3) Creating the relative acoustic impedance attribute, (4) Geometrical modelling. The seismic modeling provided information about the variations of the seismic wavelet properties (Amplitude, frequency …etc.) along the interpreted horizons, thus it allowed additional options in dealing with the seismic data. As a result of this study, 3D sedimentary model was built for the Permian Period, Early Triassic Epoch, and the Middle Triassic Epoch. 3D model for the post-Miocene Epoch was also built and showed the 3D representation of the Kurrachine Dolomite Formation. It also showed the locations of the main igneous intrusions which were found out by Shaheen et al., 2018.